Using of FAHP and fuzzy TOPSIS techniques for prioritising of Iranian banks to customer relationship management factors. (2017) - Maymand, Mohammad Mahmoudi; Keshavarz, Elham
The purpose of this research is to realise how organisations have been sustaining their growth through applying customer relationship management. Considering that Mellat, Melli and Central Saderat banks in Semnan have been brought for this research as statistic population, the number of experts participating in the study is 30 persons who were interested in improving discussion. The main tools used for gathering the data in this study were bank records and questionnaire. In this study, banks including private bank, state-owned bank, semi-private bank were ranked regarding to sub-scales related to different levels of customer relationship management factors and strategy, organisational performance, customer, process, infrastructure, technology sub-criteria of banking industry by using fuzzy analytic hierarchy process (FAHP) and fuzzy TOPSIS. The results obtained from both methods indicate that private bank is more important than semi-private bank and owned state bank in the banking industry. According to the customer relationship management factors, it is concluded that strategy is superior to other factors and then customer, organisational performance, process, infrastructure and technology are at the next rank, respectively. According to the strategy scale, it is concluded that strategic alliance is more important than other factors.